Aglossia: Case Report - Bommarito,Silvana (2016)
Introduction Aglossia is a rare condition caused by failure of the tongue embryogenesis process (in the fourth to eighth weeks of gestation). The tongue is an organ used in different activities such as sucking, swallowing, chewing, and talking. It is also responsible for shaping palate dental arches (in its absence, they become atrophic). There are few similar cases reported in the literature. Objective To describe a rare case of aglossia and the multidisciplinary professionals working together for 5 years to treat the patient. Resumed Report An 8-year-old girl with aglossia had an assessment comprising: (1) clinical assessment of the stomatognathic system related to resting posture, tonus, and mobility; (2) orthodontic assessment; (3) surface electromyography of the chewing muscles; (4) swallowing videofluoroscopy. Conclusion The authors confirmed the need of multidisciplinary cooperation to improve the patient s quality of life, because agenesia implicates many activities/ functions that depend on the tongue to fully work. Multiprofessional cooperation helps the patient learn compensation mechanisms.